KOMUNIKASI ANTARBUDAYA MAHASISWA DALAM MEWUJUDKAN KEHARMONISAN DI LINGKUNGAN KAMPUS - WIBAWA, RESDHI; SUMARWAN, EDI (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2023)
Differences in student culture result in differences in the way of communication in conveying ideas, ideas, and daily behavior. This research aims to see the intercultural communication patterns of students in the STIAB Jinarakkhita environment. This research uses a descriptive qualitative approach, with data collection methods of observation, interviews and documentation. Data collection focused on six informants who came from various regions. The results showed that intercultural communication patterns that occur in students at STIAB Jinarakkhita are strongly influenced by ethnic factors, language, and social environment. Students tend to use local languages when communicating with people who have the same ethnic background, but use Indonesian when mingling with people of different ethnicities. Verbal communication is the most frequent communication pattern, but communication symbols remain an important part of intercultural communication. In addition, social media such as WhatsApp is also used as a means of communication, especially if you cannot meet directly on campus. It is hoped that understanding the intercultural communication patterns at STIAB Jinarakkhita can contribute to the development of a more inclusive multicultural education. As well as enriching the learning experience for all students in higher education institutions that have cultural diversity. ABSTRAKPerbedaan budaya mahasiswa mengakibatkan perbedaan cara komunikasi dalam menyampaikan ide, gagasan, dan perilaku sehari-hari. Penelitian ini bertujuan untuk melihat pola komunikasi antarbudaya mahasiswa di lingkungan STIAB Jinarakkhita. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan metode pengumpulan data observasi, wawancara dan dokumentasi. Pengambilan data difokuskan pada enam Informan yang berasal dari berbagai daerah. Hasil penelitian menunjukan pola komunikasi antarbudaya yang terjadi pada mahasiswa di STIAB Jinarakkhita sangat dipengaruhi oleh faktor etnis, bahasa, dan lingkungan sosial. Mahasiswa cenderung menggunakan bahasa daerah ketika berkomunikasi dengan orang yang memiliki latar belakang suku yang sama, namun menggunakan bahasa Indonesia ketika berbaur dengan orang dari suku yang berbeda. Komunikasi verbal menjadi pola komunikasi yang paling sering dilakukan, namun simbol-simbol komunikasi tetap menjadi bagian penting dalam komunikasi antarbudaya. Selain itu, media sosial seperti WhatsApp juga digunakan sebagai sarana komunikasi, terutama jika tidak dapat bertemu langsung di kampus. Diharapkan dengan memahami komunikasi antarbudaya di STIAB Jinarakkhita dapat memberikan kontribusi dalam pengembangan pendidikan multikultural yang lebih inklusif. Serta memperkaya pengalaman belajar bagi seluruh mahasiswa di institusi pendidikan tinggi yang memiliki keanekaragaman budaya.